The effects of oil palm plantations on the functional diversity of Amazonian birds. (5th August 2016) - Almeida, Sara M.; Silva, Larissa C.; Cardoso, Maíra R.; Cerqueira, Pablo V.; Juen, Leandro; Santos, Marcos P. D.
Abstract: Oil palm plantations are rapidly expanding in tropical areas, although the nature of the impacts on the functional roles of the different species in the ecosystem is poorly understood. The present study is the first assessment of how oil palm affects the functional diversity of birds in the Brazilian Amazon and tests the hypothesis that converting forest to oil palm decreases functional diversity of bird communities, selecting species more tolerant to environmental disturbances. We conducted point counts to survey bird communities in 16 plots in the eastern Amazon. We sampled 32 points in riparian forest, 128 in oil palm and 160 in forested habitats. To test whether the conversion of forest into oil palm plantations affects functional diversity of birds we calculated the FD (Functional Diversity) and FRic (Functional Richness) indices. To examine whether oil palm plantations select species functionally more similar than expected by chance we used a null model (SES.FD). FD was significantly higher in the forest plots in comparison with riparian forests and oil palm, and lower in oil palm when compared with riparian forests. FRic, in turn, was greater in forest plots than in oil palm and in riparian forest. These results show that the conversion of forested areas to oil palm represents a great loss of functional strategies. The SES values indicate that in forested habitats bird communities tend to be functionally clustered while in the oil palm they are functionally overdispersed. The functional traits most affected by oil palm were those associated with diet and foraging stratum. In short, oil palm plantations reduced functional diversity of birds, although the presence of riparian forests within the plantations and the fragments of forest adjacent are extremely important for the maintenance of ecosystem services.